MISI GEREJA KATOLIK MASA KINI: KECERDASAN ARTIFICIAL YANG MEMANUSIAKAN MANUSIA (Implementasi Tujuh Karunia Roh Kudus Menurut Santo Agustinus) - Ranubaya, Fransesco Agnes (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
The focus of this research is to analyze the ethical aspects and identify the potential for practical implementation of the seven gifts of the Holy Spirit according to Saint Augustine in the use of humanizing artificial intelligence. This research aims to analyze the ethical aspects of the implementation of the seven gifts of the Holy Spirit according to Saint Augustine in the context of artificial intelligence (AI) and identify the strengths and opportunities associated with their practical use. This research method uses a philosophical analysis approach to Saint Augustine's thoughts on the seven gifts of the Holy Spirit as well as their application in the development of humanizing AI. The results show that the practical implementation of the seven gifts of the Holy Spirit in AI has great potential to produce technology that is oriented towards justice, equality, and improving the quality of life. The power of AI in accelerating decision-making and improving efficiency is also highlighted as an important factor. The main conclusion of this study is that an ethical approach based on religious values can be a valuable guide in the development and application of AI technologies that are mindful of human well-being.